Application Progress of Food 4D Printing Technology in Food Industry - Qiang TONG; Shuailei XIAO; Ye BI; Hao WU; Xiuping DONG (Shipin gongye ke-ji)
4D printing technology, as an emerging printing technique that adds the dimension of "time" to 3D printing, not only enables the construction of complex structures in three-dimensional space but also allows for self-assembly and shape transformation of printed objects through pre-programmed material deformation. As a next-generation additive manufacturing technology, 4D printing is gaining increasing potential and influence due to its completely predictable, designable, and controllable evolutionary process. In recent years, 4D printing technology has also been widely researched and applied in modern food processing, enabling precise control of food structure, nutritional composition, texture, and other characteristics through 4D printing. This paper reviews the principles, elements, and advantages of food 4D printing technology, analyzes the progress of food 4D printing applications in modern food processing, including 4D printing material properties and external stimuli conditions. It particularly discusses the relationship between microstructure control of 4D printed smart foods and texture. Finally, it outlines the development trends and challenges of food 4D printing technology, aiming to provide a reference for modern food processing.